Expressive Speech Acts in the Comments Column of Erick Thohir's Tiktok Account - Marsela, Jeny; Asnawi, Asnawi (Jurnal Sastra Indonesia, 2024)
The aim of this research is to describe expressive speech in writing through the comments column of the Tiktok account @Erick Thohir. This research uses qualitative research using descriptive methods. The data source in this research is attached through documentary evidence in the form of screenshots of findings from comments obtained in Erick Thohir's Tiktok account post with the topic "For the Future of the U20 National Team Players who have worked hard, for the sake of supporters who want to see football Indonesia at World Level”. Data collection techniques include observation techniques, identifying comments, and analyzing data. The results of this research show expressive speech functions of expecting, thanking, complaining, praising, and sarcasm. Of the 123 utterances found, the utterance most frequently used by speakers in the TikTok comment column @Erick Thohir has the expressive function of expecting speech, namely with 61 data. Apart from that, there are 27 expressive speech functions of thank you, 11 expressive speech functions of complaining, 8 expressive speech functions of praising, and 17 expressive speech functions of sarcasm. It was found that there were many expressive speech functions of hope due to the many people's hopes regarding Indonesia remaining as the host of the U-20 World Cup. People communicate their psychological attitudes through expressive speech functions expecting the consequences of FIFA's decision to cancel Indonesia as host of the world cup.